TI_GERICHTE 52.2019.609 vom 23. Oktober 2019 , Licenza edilizia per la costruzione di un lift e di un parcheggio - TI Tribunale d'appello (2019)
Licenza edilizia per la costruzione di un lift e di un parcheggio